Vibrational spectra of the rare‐occurring complex hydrogen arsenate minerals pharmacolite, picropharmacolite, and vladimirite: Dominance of Raman over IR spectroscopy to discriminate arsenate and hydrogen arsenate units. (18th January 2018) - Makreski, Petre; Todorov, Jovica; Makrievski, Vasil; Pejov, Ljupčo; Jovanovski, Gligor
Abstract: This work represents the first complete experimental and theoretical study of the infrared (IR) spectra of pharmacolite, Ca(AsO3 OH)·2H2 O; vladimirite, Ca4 (AsO3 OH)(AsO4 )2 ·4H2 O; and picropharmacolite, Ca4 Mg(AsO3 OH)2 (AsO4 )2 ·11H2 O. IR spectra, collected at both room and liquid nitrogen temperature, have shown similar spectral view among minerals in the region of ν1 to ν4 modes, surprisingly not involving complexity in vladimirite and picropharmacolite spectral view due to the presence of both AsO3 OH and AsO4 units compared to pharmacolite where only AsO3 OH units appear in the structure. On the other hand, vladimirite and picropharmacolite Raman spectra in the corresponding ν1 to ν4 region (955–350 cm −1 ) exhibit existence of 3 sets of 2 bands (6 in total) completely reflecting the existence of 3 symmetrically nonequivalent AsO4 groups in the structures of vladimirite and picropharmacolite (of which one is protonated) and only one set of ν1 to ν4 bands from the structurally equivalent AsO3 OH units in the pharmacolite structure. The liquid nitrogen temperature IR spectra enabled to infer important information regarding the OH vibrational bands related to the AsO3 OH groups and to the water molecules. Essentially, all bands in the vibrational spectra were assigned and correlated with the findings for a plethora of structurally similar complex hydrogen arsenate minerals. To support the tentative assignment of bands in the vibrational spectra, quantum theoretical calculations were performed within the framework of density functional theory. On the basis of theoretical calculations, a few reassignments of bands appearing in the OH stretching region are proposed. X‐ray powder diffraction was used to confirm authenticity of the title systems. Abstract : Raman spectra depicted three sets of two bands in the region of ν1 to ν4 modes completely reflecting the existence of three symmetrically nonequivalent AsO4 groups in vladimirite and picropharmacolite (of which one is protonated) and only one set of ν1 to ν4 bands from the structurally equivalent AsO3 OH units in pharmacolite. On the basis of theoretical calculations, reassignments of few bands in the region of OH stretching vibrations due to the crystalline water molecules and hydrogen arsenate anions were proposed.